The use of assisted autogenic drainage in children with acute and chronic respiratory disease - Corten, Lieselotte (Division of Physiotherapy, 2017)
Background: Respiratory problems, both acute and chronic, remain an important cause of disease burden for children worldwide. Airway clearance techniques, as part of the management of these conditions, might influence the course of the disease thereby reducing this burden. Objective: This PhD thesis aimed to explore the epidemiology and management of children with acute respiratory diseases admitted to a paediatric hospital in Cape Town, South Africa; and to determine the usefulness and safety of assisted autogenic drainage in children with an acute (pneumonia) or chronic (cystic fibrosis) respiratory disease. In order to do this, several linked studies were undertaken including a retrospective folder review, two systematic reviews and two pragmatic randomised controlled trials.